Factors that Influence Banking Performance in Indonesia - Maria Albertina Dewanti Eston; Putut Jatmiko; Henny Setyo Lestari; Farah Margaretha Leon (International Journal Labs, 2023)
This research aims to examine the influence of ESG Score, NPL, Bank Size, Bank Capital, Liquidity Risk, Bank Liquidity, revenue growth, Bank Leverage, Economic Growth, Inflation, Diversification, Labor Productivity, and ESG Score Moderating on Bank performance, which is shown with the achievement of Return on Assets. The research sample used in this research is banks listed on the Indonesia Stock Exchange for the period 2018 to 2022. Data was taken from time series data which contains data from 2018 to 2022 for the independent variable and bank performance as the dependent variable. The research methodology used is Ordinary Least Squares using Eviews 12 software. The findings and contributions in this research are that ESG Score, Non-Performing Loans, Bank Leverage, Economic Growth, and Inflation influence bank performance. Meanwhile, Bank Size, Bank Capital, Liquidity Risk, Bank Liquidity, and revenue growth do not have a significant effect on changes in bank performance. Bank Leverage, Economic Growth, and Inflation have a positive and significant effect on changes in bank performance, while ESG Score and Non-Performing Loans have a negative and significant effect on changes in bank performance. Banks can take advantage of Bank Leverage, Economic Growth, and Inflation opportunities to improve their performance so that investors are interested in buying bank shares. Low and controlled Non-Performing Loans will increase banking profits, thereby improving the bank's performance. It is hoped that the results of this research can provide input for banks and investors to consider ESG Score, Non-Performing Loans, Bank Leverage, Economic Growth, and Inflation in managing their business and in making investment decisions.